'I get my income from sharing.' Modelling satisfaction of peer service providers on capital and labour sharing economy platforms. (June 2022) - Akhmedova, Anna; Mas-Machuca, Marta; Marimon, Frederic
Abstract: Peer (service) providers (PPs) are the frontline actors on sharing economy platforms (SEPs), and to date have received very limited attention in academic literature. These actors enter in economic exchanges with other stakeholders in the platform ecosystem by giving access to their underutilized assets – both tangible (vehicles, accommodation, clothes, etc.) and intangible (skills, time, etc.). Monetary compensation is the immediate and obvious benefit that these actors obtain. However, it has been shown that extrinsic benefits might not be sufficient to outweigh the evident costs associated with platform governance and spot-based transactions. This research is one of the first attempts to explore the satisfaction and loyalty of PPs, comparing capital and labour sharing platforms. We build on the social exchange theory and cost–benefit approach, developing the PP satisfaction model. Using structural equation modelling we analyse data from 205 PPs. We find that satisfaction with the platform and with the role of PP are related to loyalty. Sensitivity to the peer-to-peer business model is developed as a result of experiences and also impacts on loyalty. Graphical abstract: Image 1